Laboratory Evolution Experiments Help Identify a Predominant Region of Constitutive Stable DNA Replication Initiation - Reshma T. Veetil (American Society for Microbiology, 2020)
ABSTRACT The bacterium Escherichia coli can initiate replication in the absence of the replication initiator protein DnaA and/or the canonical origin of replication oriC in a ΔrnhA background. This phenomenon, which can be primed by R-loops, is called constitutive stable DNA replication (cSDR). Whether DNA replication during cSDR initiates in a stochastic manner through the length of the chromosome or at specific sites and how E. coli can find adaptations to loss of fitness caused by cSDR remain inadequately answered. We use laboratory evolution experiments of ΔrnhA-ΔdnaA strains followed by deep sequencing to show that DNA replication preferentially initiates within a broad region located ∼0.4 to 0.7 Mb clockwise of oriC. This region includes many bisulfite-sensitive sites, which have been previously defined as R-loop-forming regions, and includes a site containing sequence motifs that favor R-loop formation. Initiation from this region would result in head-on replication-transcription conflicts at rRNA loci. Inversions of these rRNA loci, which can partly resolve these conflicts, help the bacterium suppress the fitness defects of cSDR. These inversions partially restore the gene expression changes brought about by cSDR. The inversion, however, increases the possibility of conflicts at essential mRNA genes, which would utilize only a minuscule fraction of RNA polymerase molecules, most of which transcribe rRNA genes. Whether subsequent adaptive strategies would attempt to resolve these conflicts remains an open question. IMPORTANCE The bacterium E. coli can replicate its DNA even in the absence of the molecules that are required for canonical replication initiation. This often requires the formation of RNA-DNA hybrid structures and is referred to as constitutive stable DNA replication (cSDR). Where on the chromosome does cSDR initiate? We answer this question using laboratory evolution experiments and genomics and show that selection favors cSDR initiation predominantly at a region ∼0.6 Mb clockwise of oriC. Initiation from this site will result in more head-on collisions of DNA polymerase with RNA polymerase operating on rRNA loci. The bacterium adapts to this problem by inverting a region of the genome including several rRNA loci such that head-on collisions between the two polymerases are minimized. Understanding such evolutionary strategies in the context of cSDR can provide insights into the potential causes of resistance to antibiotics that target initiation of DNA replication.